Meningkatkan Ekonomi Makro Perusahaan dengan Menerapkan Konsep Manajemen Sumber Daya Manusia - Mumun Nurchasanah; Pompong Budi Setiadi; Sri Rahayu (Universitas Islam Kadiri, 2022)
The purpose of this study is to analyze in improving the company's macroeconomics by applying the concept of human resource management. Macroeconomics not only has an impact on companies but there are also economic changes in household businesses (households) and market businesses. The research method used is qualitative. Data collection techniques use documentary techniques by collecting information from written documents, especially in the form of research images on research problems. Based on the research results, it can be concluded that human resources perform their duties as a department with personnel management expertise available in the company to achieve the goals of efficiency and profitability of the company's business operations. Macroeconomics has a causal relationship that is studied in macroeconomics is basically the relationship between aggregate economic variables (overall), such as payments, national capital stock, government debt, and others.